Agricultural value chains: How cities reshape food systems - Minten, Bart; Reardon, Thomas; Chen, Kevin Z. (International Food Policy Research Institute, 2017)
Rapid growth of cities is driving change in agricultural value chains—key factors include increased commercial flows of agricultural goods, diet transformation, and the large role of commercial markets in meeting urban food needs. Megacities in developing countries are transforming value chains for high-value crops and for traditional staple food crops. The “quiet revolution” affecting staple-food value chains is increasing productivity through: Increased investment in technology and modern inputs, including fertilizers and improved seeds, by farmers close to cities. Use of mobile phones by farmers to better position themselves in markets. Greater vertical integration resulting from the growing scale of midstream and retail sections of the value chain—such as cold storage, rice mills, and supermarkets.